The Hannover Postinfarction Ventricular Septal Rupture Score: A New Scoring System Predicting 30-Day Mortality - Lisa Baustert; Dietmar Boethig, MD; Adelheid Görler, MD; Christian Kühn, MD; Alexander Weymann, MD; Bastian Schmack, MD; Aron-Frederik Popov, MD; Arjang Ruhparwar, MD; Bettina Wiegmann, MD (CJC Open)
Background: Because of the increasing importance of quality assurance and individualised patient treatment, EuroSCOREs were analysed for reliability in predicting 30-day mortality in patients with postinfarction ventricular septal rupture (piVSR). To address the specific conditions of patients with piVSR, the Hannover piVSR Score (HpiVSR) was developed. Methods: Between 2001 and 2019, 45 patients with piVSR underwent surgery. Data were collected as necessary for EuroSCORE calculation. Clinically relevant variables were validated for the HpiVSR Score using a nonparsimonious binary logistic regression model. All models were tested for their significant predictive power for 30-day mortality. Their validity was assessed using Hosmer-Lemeshow test and Nagelkerke R2. Receiver operating characteristic curve and area under the curve were used to illustrate and quantify score accuracy. Results: The specificity was 77.8% for all EuroSCOREs and 92.6% for the HpiVSR Score, and the sensitivity was in the random range for the EuroSCOREs and 83.3% for the HpiVSR Score. Accordingly, the areas under the curve were 0.676 (95% CI 0.507-0.845) for EuroSCORE II; 0.729 (95% CI 0.581-0.878) and 0.739 (95% CI 0.591-0.886) for the additive and logistic EuroSCORE, respectively; and 0.949 (95% CI 0.891-1.006) for the HpiVSR Score. Conclusion: The HpiVSR Score enables a more reliable and accurate prediction of 30-day mortality than the EuroSCOREs using 7 significant, objective, reliable, and preoperatively determinable variables. Because of the small sample size of the present study and the fact that only internal validation has been performed so far, the weighting of the factors of the HpiVSR Score can be adjusted after studies with larger patient samples. Résumé: Contexte: En raison de l'importance croissante de l'assurance qualité et du traitement personnalisé des patients, les indices EuroSCORE ont été analysés pour déterminer leur fiabilité dans la prédiction de la mortalité à 30 jours chez les patients souffrant d'une rupture du septum ventriculaire post-infarctus (RSVpi). Le score RSVpi de Hanovre (RSVpi-H) a été développé pour répondre aux conditions spécifiques des patients atteints de RSVpi. Méthodes: Entre 2001 et 2019, 45 patients atteints de RSVpi ont été opérés. Les données nécessaires au calcul des EuroSCORE ont été recueillies. Les variables pertinentes cliniquement ont été validées pour le score RSVpi-H à l'aide d'un modèle de régression logistique binaire non paramétrique. Tous les modèles ont été testés pour leur pouvoir prédictif significatif de la mortalité à 30 jours. Leur validité a été évaluée à l'aide du test de Hosmer-Lemeshow et du R2 de Nagelkerke. La courbe représentant la fonction d’efficacité du récepteur et l'aire sous la courbe ont été utilisées pour illustrer et quantifier la précision du score. Résultats: La spécificité était de 77,8 % pour tous les EuroSCORE et de 92,6 % pour le score RSVpi-H, et la sensibilité se situait dans la plage aléatoire pour les EuroSCORE et de 83,3 % pour le score RSVpi-H. En conséquence, les aires sous la courbe étaient de 0,676 (intervalle de confiance [IC] à 95 % 0,507-0,845) pour l'EuroSCORE II; 0,729 (IC à 95 % 0,581-0,878) et 0,739 (IC à 95 % 0,591-0,886) pour les EuroSCORE I additif et logistique, respectivement; et 0,949 (IC à 95 % 0,891-1,006) pour le score RSVpi-H. Conclusion: Le score RSVpi-H permet une prédiction plus fiable et plus précise de la mortalité à 30 jours que les EuroSCORE en utilisant 7 variables significatives, objectives, fiables et déterminables en préopératoire. En raison de la petite taille de l'échantillon de cette étude et du fait que seule une validation interne a été effectuée jusqu'à présent, la pondération des facteurs du score RSVpi-H peut être ajustée après des études portant sur des échantillons de patients plus importants.